SOCIALIZATION OF THE APPLICATION OF WASP NEST BRIQUETTE TECHNOLOGY FROM LOCAL SAGO WASTE IN YAKONDE VILLAGE, WAIBU DISTRICT, JAYAPURA REGENCY - Agustinus Agustinus; Pither Palamba; Enos Tambing; Elisabeth Payung Allo; Inggrid Nortalia Kailola (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
Yakonde Village in Waibu District boasts abundant natural food resources, including sago palms (Metroxylon sagu Rottb), which grow wild throughout the lowlands. The potential for local raw materials, such as sago pulp waste, is enormous, but only a small portion is used for fuel briquettes. Therefore, empowerment and development strategies are needed for local communities, aiming to provide training in utilizing this waste. Through this outreach, local communities can create alternative fuels from this waste, thereby reducing dependence on fossil fuels and addressing fuel shortages. Sago pulp waste is a product that can increase local income by turning it into charcoal briquettes.